Fabrication of catalyst coated membrane with screen printing method in a proton exchange membrane fuel cell - Wang, Wentao; Chen, Shunquan; Li, Jianjun; Wang, Wei (International journal of hydrogen energy, 2015)
A new proton exchange membrane fuel cell catalyst paste based on direct screen printing was developed to fabricate membrane electrode assembly (MEA) with catalyst coated membrane (CCM) technique. A mixture of cyclohexanol and ethylene glycol was found to be the best solvent for the screen printing catalyst paste in terms of avoiding the swelling of K+ form Nafion® membrane and mud-cracking in the catalyst layer during the CCM-MEA fabrication process and improving adhesion between the Nafion® membrane and catalyst layers. The CCM-MEAs fabricated with this new catalyst paste with the direct screen printing method showed better or comparable performance with the same or much less catalyst loading compared with that of MEA fabricated with a gas diffusion electrode (GDE) technique. An empirical relationship was provided to determine the amount of solvents used for the catalyst paste. Criteria were also proposed to choose the potentially suitable solvents. The other factors which might affect the performance of the screen printed CCM-MEAs were also examined. The low cell voltage decay rate and the relatively high performance of the screen printed CCM-MEAs demonstrated that the direct screen printing method with the proposed new catalyst paste could be a beneficial complement to the conventional CCM fabrication technique. •A novel screen printing paste for fabrication of MEA via CCM technique is reported.•A CCM fabrication procedure based on the screen printing paste is presented.•Criteria for choosing the right solvents for screen printing paste are proposed.•Effects of pre-treatment and post-treatment on the CCM-MEA have been examined.•CCM-MEAs show better or comparable performance compared with that of GDE-MEAs.